Improve Teacher Community Knowledge on Creating Instructional Video as Media Center based on Social-Network in SMPN 20 Jakarta - Rifiana Arief; Widyo Nugroho; Erlina Solihin (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
Due to Covid-19 pandemic, learning activities turn into online. Online learning requires a media that can maximize the delivery of material and thus students can understand independently. Teachers should improve their ability to use information technology and creativ to create a good learning video which is worth to upload and deserves copyright recognition. The method is to provide the mentorship. Mentorship purpose is to assist teachers to produce learning videos that are suitable being uploaded on YouTube and receive recognition of the copyrighted videos. As a result of these mentorships, the participants succeed in creating a learning video with a variety of material topics which can be uploaded in Youtube and receive recognition of copyright ownership. Thereafter, the school can manage independently and continue to enrich content of school's YouTube channel and increase the number of copyright for teacher's video works.